Podchody k uglublennoj individualizacii i technologii monitoringa podgotovki igrokov v svjazi s problemoj olimpijskogo otbora - Radcic, I. Ju. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The analysis of results of the largest international competitions for the last five years has shown, that world sports in game kinds put forward high and versatile requirements to the level of preparedness of the strongest players, and put new difficult theoretical and practical tasks before the complex of sciences about the game activity. Achievements of a science and the recommendations turn to the important factor of growth of sports results.